Aflasafe-IITA English - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2020)
To feed the growing global population, we need to not only increase production but also ensure safe food free from aflatoxin contamination. In this video, we explain @IITA_CGIAR comprehensive strategy to control aflatoxin including the use of #aflasafe technology